Trans-border land acquisitions: A new guise of outsourcing and host country effects - Gouranga Das (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
The rush for land acquisition - primarily driven by food shortages, food price volatility, and the run for agrofuel - has drawn considerable attention, as documented by reports published in late 2009, 2010, and 2011. Terminological differences aside, it is - quite distinct from material or service outsourcing - a kind of off-shoring farm production across borders to relatively land-abundant nations and exporting it back to mitigate the adverse effects of food insecurity. While the academic literature is not capacious, this paper, the first of its kind, attempts to study its (potential) effects in the context of a small open economy subject to exogenous shocks. The presence of a sector subject to land acquisition is central to the analysis. In particular, the paper notes that: (i) an increase in world prices of agro-business sector causes skewed effects (shrinkage) in manufacturing or innovative sectors, and subsistence sector (via forward and backward linkages), causing price change vulnerability; (ii) with attractive premiums offered by host country, land acquisition will undermine the avowed objective of mitigating food shortages and aggravate income inequality; (iii) technological progress or inducing technological efforts via skills, capacity building, and infrastructure development will have positive effects if host countries adopt a policy climate favourable to fostering governance and education for revitalizing agriculture. Further extensions to address pertinent (stylized) facts are also explored.
Keywords: F22; J31; O15; 330; land deals; food prices; land premium; wage gap; immiserizing deals